2009
DOI: 10.5014/ajot.63.5.549
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Dynamic Interactional Model in Self-Care and Motor Intervention After Traumatic Brain Injury: Explanatory Case Studies

Abstract: These research findings contribute to our theoretical knowledge in rehabilitation and promote adopting this approach for rehabilitation of adolescents with TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Children's involvement in the identification of their needs and the selection of their intervention goals is likely to increase their motivation to learn, thereby promoting academic achievement (Graham et al, 2013;Schunk, 1996). Thus, tools that enable student self-assessment and goal setting may elicit more powerful and enduring levels of student engagement in the learning environment (Toglia, 2011;Zlotnik, Sachs, Rosenblum, Shpasser, & Josman, 2009). However, this key component often is missing in formal handwriting assessment and intervention.…”
mentioning
confidence: 99%
“…Children's involvement in the identification of their needs and the selection of their intervention goals is likely to increase their motivation to learn, thereby promoting academic achievement (Graham et al, 2013;Schunk, 1996). Thus, tools that enable student self-assessment and goal setting may elicit more powerful and enduring levels of student engagement in the learning environment (Toglia, 2011;Zlotnik, Sachs, Rosenblum, Shpasser, & Josman, 2009). However, this key component often is missing in formal handwriting assessment and intervention.…”
mentioning
confidence: 99%
“…Two studies (Henshaw et al, 2011;Polatajko et al, 2012) addressed occupational performance through cognitive means (discussed in the next paragraph). In all, 12 studies used the COPM as an assessment tool (Beckelhimer et al, 2011;Ciro et al, 2013;Hayner et al, 2010;Henshaw et al, 2011;Hermann et al, 2010;Jack & Estes, 2010;McCall et al, 2011;Nilsen et al, 2012;Polatajko et al, 2012;Skubik-Peplaski et al, 2012;Wu et al, 2011;Zlotnik et al, 2009). Several research investigations conducted over the past 5 yr tested cognitive-based approaches.…”
Section: Descriptive; Anovasmentioning
confidence: 99%
“…Hall et al (2013) evaluated whether a conservative approach to treatment of carpal tunnel syndrome would reduce surgical intervention and found that patients in the conservative intervention group reported greater symptom relief. Similarly, a tailored approach to activity pacing was found to be superior to a general approach when used for people with osteoarthritic joint stiffness (Schepens et al, 2012), and Zlotnik et al (2009) reported that the Dynamic Interactional Model of intervention was effective in meeting the special needs of two teenagers with TBI. Guidetti et al (2009) conducted a survey related to the role of context in regaining self-care skills after stroke or spinal injury, and Hand et al (2011) and Kim and Colantonio (2010) produced two literature reviews on community-based intervention.…”
Section: Descriptive; Anovasmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized clinical trial, Goverover and colleagues demonstrated that multicontextual treatment results in improved self-regulation and functional performance on instrumental activities of daily living after brain injury [79]. In addition, Zlotnik and colleagues presented two case examples in which the individuals had impaired awareness of their cognitive and motor impairments post-brain injury [80]. After several weeks of multicontextual treatment, both individuals demonstrated improvements in self-care, mobility and graphomotor abilities, as well as being able to identify deficits in these functional activities.…”
Section: Interventions For Anosognosia For Hemiplegiamentioning
confidence: 99%